2012
DOI: 10.36251/josi.55
|View full text |Cite
|
Sign up to set email alerts
|

What does the literature say about resilience in refugee people? Implications for practice

Abstract: Refugee people experience many trials prior to arriving in Australia and face ongoing challenges associated with re-settlement. Despite facing such difficulties many refugee people demonstrate enormous strength and resilience that facilitates their re-settlement process. The authors' experience however suggests that professionals working with refugee people tend to focus on the trauma story to the neglect of their strengths. At times this means resilience is overshadowed by a dominant Western deficits model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 32 publications
(35 reference statements)
5
97
1
4
Order By: Relevance
“…Early work in resilience research and still much of the focus today, centres on the negative effects of adversity and the psychology of individual responses to adverse situations or conditions (Hutchinson and Dorsett, 2012;Luthar et al, 2000;Masten and Wright, 2010). The locus of this research is primarily focused on risk factors in relation to chronic illnesses in adults, and vulnerability in relation to children (Pooley and Cohen, 2010, p. 30).…”
Section: How Is Resilience Conceptualised?mentioning
confidence: 99%
See 2 more Smart Citations
“…Early work in resilience research and still much of the focus today, centres on the negative effects of adversity and the psychology of individual responses to adverse situations or conditions (Hutchinson and Dorsett, 2012;Luthar et al, 2000;Masten and Wright, 2010). The locus of this research is primarily focused on risk factors in relation to chronic illnesses in adults, and vulnerability in relation to children (Pooley and Cohen, 2010, p. 30).…”
Section: How Is Resilience Conceptualised?mentioning
confidence: 99%
“…When resilience is viewed as a personal quality or trait, a number of factors emerge that emphasise the affective aspects of personal character, focusing on the optimism, personal strength, adaptability and perseverance (Ahern et al, 2008;Hutchinson and Dorsett, 2012;Pooley and Cohen, 2010). As a process, resilience has been defined more holistically to include the psychological, and the interaction between the "ecological context" and the person (Curtis and Cicchetti, 2007, p. 811).…”
Section: How Is Resilience Conceptualised?mentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on religious and spiritual beliefs to regain control and meaning in one's life has also been found to be a useful coping strategy for refugees post‐migration (Khawaja et al . , Hutchingson & Dorsett ). Furthermore, a study of Somali and Oromo refugee youth in the United States found that the most frequent strategies used to combat sadness and stress were praying (55.3%), sleeping (39.9%), reading (32.2%), talking to friends (27.8%) and physical activity (10%) (Halcón et al .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, research also highlights the considerable levels of personal resilience that many people from a refugee background have and a range of coping strategies that may be utilised during their transition to the host society (Correa-Velez et al 2010, Fozdar & Hartley, 2013Hutchinson & Dorsett 2012, Goodman 2004, Pittaway et al 2009, Schweitzer et al 2007, Silove 2001. This research predominately focuses on refugees' post-migration experiences (that is, those who have been granted refugee status), which raises important questions as to how asylum seekers cope with ongoing uncertainty while they wait for their refugee claim to be finalised, and the types of coping strategies they may engage in.…”
Section: Introductionmentioning
confidence: 99%